PENGARUH MOTILITAS SPERMATOZOA SEMEN BEKU SAPI PERAH BERPENGERCER SUSU SKIM DENGAN METODE THAWING YANG BERBEDA - Fachroerrozi Hoesni (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Research conducted at the Faculty of Animal Reproduction Laboratory Animal Edinburgh University, on May 8 through June 15, 2014. The material used is 30 straw frozen semen from the male dairy cows BIB Lembang. Materials and tools used are thermometer, microscope, glass objects, cover glass, container of liquid nitrogen gas, water bath, micropipette, stop watch, scissors, tissue rolls.The experimental design used was a completely randomized design (CRD) with 4 treatments (P1, P2, P3, P4) and 6 replicates, The treatment is P1: room temperature 60 seconds, P2: Temperature 37 ° C for 30 seconds, P3: temperature of 50 ° C for 12 seconds and P4 temperatures of 70 ° C for 8 seconds.From the research shows that the thawing of frozen semen FH cows at room temperature for 60 seconds and 37 ° C for 30 seconds produces better sperm motility than other treatments, so that the lower the level of decline compared with the results obtained lower motility, the rate higher losses.Based on the results of this study concluded that long and thawing temperatures affect sperm motility, motility best is at 37 ° C for 30 seconds and room temperature for 60 seconds.Keyword : spermatozoa, dairy cows, thawing method